Comparative clinical outcome following individualized follitropin delta dosing in Chinese women undergoing ovarian stimulation for in vitro fertilization /intracytoplasmic sperm injection - Rui Yang; Yunshan Zhang; Xiaoyan Liang; Xueru Song; Zhaolian Wei; Jianqiao Liu; Yezhou Yang; Jichun Tan; Qingxue Zhang; Yingpu Sun; Wei Wang; Weiping Qian; et al. (figshare, 2022)
Abstract Background To compare the efficacy and safety of follitropin delta in its individualized fixed-dose regimen with follitropin alfa in a conventional adjustable dosing regimen in Chinese women.  Methods This was a subgroup analysis of the randomized, multi-center, assessor-blind, non-inferiority trial (GRAPE) including 759 Chinese women (aged 20–40 years) recruited in 16 reproductive medicine clinics in China. Women were randomized in a 1:1 ratio to be treated with either follitropin delta dose based on anti-Müllerian hormone (AMH) and body weight or conventional dosing with follitropin alfa following a gonadotropin-releasing hormone (GnRH) antagonist protocol. The primary outcome was ongoing pregnancy rate assessed 10–11 weeks after embryo transfer in the fresh cycle (non-inferiority margin -10.0%). Results 378 in the follitropin delta group and 381 in the follitropin alfa group were randomized and exposed. Non-inferiority was confirmed with respect to ongoing pregnancy with rates of 31.0% vs. 25.7% for follitropin delta compared to follitropin alfa, estimated mean difference of 5.1% (95% confidence interval (CI) -1.3% to 11.5%). The clinical pregnancy rate (35.4% vs. 31.5%, P = 0.239) and live birth rate (31.0% vs. 25.5%, P = 0.101) were comparable between the follitropin delta group and the follitropin alfa group. Overall, the individualized follitropin delta treatment resulted in fewer oocytes retrieved compared to follitropin alfa treatment (10.3 ± 6.2 vs. 12.5 ± 7.5, P < 0.001), which was mainly due to fewer oocytes (10.5 ± 6.4 vs. 13.9 ± 7.8) in women with AMH ≥ 15 pmol/L. Accordingly there was a lower incidence of early ovarian hyper-stimulation syndrome (OHSS) and/or preventive interventions (6.1% vs. 11.0%, P = 0.013). A daily follitropin delta dose of 10.2 µg (95% CI: 9.3—11.2 µg) was estimated to provide the same number of oocytes retrieved as a starting dose of 150 IU/d of follitropin alfa. Conclusion Follitropin delta in its individualized fixed-dose regimen showed similar efficacy and improved safety compared with follitropin alfa in a conventional adjustable dosing regimen in Chinese women. Clinical trial registration number NCT03296527.
Keywords: Medicine; Cell Biology; Physiology; Pharmacology; Biotechnology; Chemical Sciences not elsewhere classified; Mathematical Sciences not elsewhere classified; Cancer